Aliyah to Israel: Immigration under Conditions of Adversity - Shoshana Neuman (Institute for the Study of Labor (IZA), 1999)
A snapshot at figures of immigration (Aliyah) to the Land of Israel (Palestine) and to the State of Israel reveals the following: between 1882-1947, in successive waves of immigration, some 543,000 Jews immigrated to Palestine, joining the 24,000 who lived there. During the first three years of statehood (1948-1950) the average annual growth rate of the Jewish population was about 24 percent, and between 1948-1952, mass immigration of 711,000 supplemented a population of 630,000. Recently, Israel witnessed a massive influx of Soviet immigrants. During 1990-1998 the Israeli population of 4.56 million was enriched by 879,486 immigrants, a growth rate of 19.3 percent. In 1991, 15,000 Jews were airlifted in one single day in ?Operation Solomon?. What were the factors that drove this unprecedented migration of Jews from around the globe to Israel? Many of the major international migration movements were largely economic in nature (the push of poverty or the pull of expected enhanced standards of living) or have been in response to persecution. While all these factors have played some role in immigration to Israel, the Israeli case is unusual in that its origins are essentially ideological. Israel has always encouraged and assisted the immigration and absorption process as part of a pro-immigration ideology and policy. Its raison d'etre was and remains the ingathering and retention of Jewish immigrants and the forging of these diverse elements into a unified nation. Israel is a country established for and administered by immigrants from diverse countries and origins. In most cases of rapid population growth, per capita income declines. This is due to adjustment problems, low productivity of immigrants and infrastructure bottle-necks. Israel was an exception. Immigration was accompanied by accelerated growth rates even though large public funds were devoted to housing, employment and social services to facilitate the direct absorption of mass immigration. As a result, per capita income which was 3,500 in 1950 surged to 17,000 in 1996 - an annual growth rate of 3.5 percent. This paper describes the major waves of immigration to Israel, starting from 1882 up to the present. For each immigration wave, its size, composition, origin and characteristics are documented. It then focuses on the process of immigrants? assimilation in the local labor market and addresses three main questions: (i) How well do immigrants adapt to the Israeli economy? (ii) What are the effects of immigration on employment opportunities and are they paying their way in the welfare state? (iii) Are population and production growth interrelated? The facts and figures lead to an overall evaluation of the immigration process and to the lessons to be learned from past experience to improve the absorption process. In particular, return migration, which reflects failure to absorb, is discussed, and the very different absorption policies of the 1950s and the 1990s are contrasted and compared. Suggestions for changes in immigration policies are discussed. An evaluation of the contribution of immigration to economic growth and of the importance of Hebrew language acquisition is also presented. The last section of this paper provides a summary and conclusions.
Keywords: J15; J61; 330; Migration; migration policy; Einwanderung; Juden; Migrationspolitik; Bevölkerungsökonomie; Soziale Integration; Geschichte; Israel